Islamic Banks Financing of FinTech Start-Ups in Oman: An Exploratory Study - Abdelghani Echchabi; Mohammed Mispah Said Omar; Abdullah Mohammed Ayedh; Welcome Sibanda (USIM Press, 2024)
JMIFR Vol.18 No.1 (June) 2021